Influência do relevo e da experiência dos operadores nos rendimentos e custos da colheita de madeira de eucalipto - Miyajima, Ricardo Hideaki [UNESP] (2015)
The mechanization in the forest area is becoming increasingly common, mainly at harvest wood, by the usage of modern and innovative machines. With this modernization comes the need of assessments, which allow more precisely defining the benefits that these machines are able to provide. The objective of this research was to evaluate the technical and cost of a whole tree harvesting system in two types of slope (wavy and flat) and with different operators (experience of time) in a eucalyptus plantation. The machines evaluated were: Feller Buncher, Skidder and Bundle Bucking. For technical evaluation, it was carried out a time and movements study, by the continuous time method, determining the operational efficiency and the yield of the components of harvesting system machines. To evaluate the cost, the calculation of operating cost and production (through ASABE method) have been take in place. The operating cost was R$548,86 h-1, R$377,10 h-1, and R$318,26 h-1 for the Feller Buncher, Skidder and Bundle Bucking, respectively. The lower production cost has been found to flat slope for the three machines. The yield was influenced by different operators, slope and distance classes (Skidder). The flat slope had a higher yield for the three machines.